The Effect of Foreign Direct Investment Spillover on The Level of Technical Efficiency in Large and Medium Manufacturing Industry in East Java - Widyananda, Ahmad Oktabri; Sari, Dyah Wulan (Journal of Developing Economies, 2020)
Foreign Direct Investment (FDI) takes an important role in the development process, especially in developing countries. The purpose of this study is to examine and analyze FDI spillover on the level of technical efficiency in the large and medium manufacturing industry in East Java. This study uses a time-varying stochastic frontier approach for firm-level panel data of the East Java manufacturing industry. The results show that all factors in this study affect the level of technical efficiency of large and medium industries in East Java. Variable foreign share, FDI horizontal spillover, and firm size have a positive influence on the technical efficiency of the industry. Whereas the variable FDI backward spillover, FDI forward spillover and the level of market concentration negatively affect the level of technical efficiency of the industry. Finally, it's needed to build synergies and sustainable relationships between products produced by domestic and foreign firms. Thus, the presence of foreign firms in East Java could have a positive impact on improving the technical efficiency of the domestic industry both at the upstream and downstream levels. Keywords: Foreign Direct Investment Spillover, Technical Efficiency, East Java Industry JEL: F21, L60, D24